Impact of 5α‐reductase inhibitor and α‐blocker therapy for benign prostatic hyperplasia on prostate cancer incidence and mortality. (24th October 2018) - Van Rompay, Maria I.; Curtis Nickel, J.; Ranganathan, Gayatri; Kantoff, Philip W.; Solomon, Keith R.; Lund, Jennifer L.; McKinlay, John B.
Abstract : Objective: To investigate the use of 5α‐reductase inhibitors (5ARIs) and α‐blockers among men with benign prostatic hyperplasia (BPH) in relation to prostate cancer (PCa) incidence, severity and mortality. Patients and Methods: A retrospective 20‐year cohort study in men residing in Saskatchewan, aged 40–89 years, with a BPH‐coded medical claim between 1995 and 2014, was conducted. Cox proportional hazards regression was used to compare incidence of PCa diagnosis, metastatic PCa, Gleason score 8–10 PCa, and PCa mortality among 5ARI users ( n = 4 571), α‐blocker users ( n = 7 764) and non‐users ( n = 11 677). Results: In comparison with both non‐users and α‐blocker users, 5ARI users had a ~40% lower risk of a PCa diagnosis (11.0% and 11.4% vs 5.8%, respectively), and α‐blocker users had an 11% lower risk of a PCa diagnosis compared with non‐users. Overall, the incidence of metastatic PCa and PCa mortality was not significantly different among 5ARI or α‐blocker users compared with non‐users (adjusted hazard ratios [HR] of metastatic PCa: 1.12 and 1.13, respectively, and PCa mortality: 1.11 and 1.18, respectively, P > 0.05 for both drugs), but both 5ARI and a‐blocker users had ~30% higher risk of Gleason score 8–10 cancer, adjusted HR 1.37, 95% confidence interval [CI] 1.03–1.82, P = 0.03, and adjusted HR 1.28, 95% CI 1.03–1.59, P = 0.02, respectively compared with non‐users. Conclusion: The use of 5ARIs was associated with lower risk of PCa diagnosis, regardless of comparison group. Risk of high grade PCa was higher among both 5ARI users and α‐blocker users compared with non‐users; however, this did not translate into higher risk of PCa mortality.